(untitled) (Vietnam Journal of Community Medicine, 2022)
Background: Continuing Medical Education (CME) is a form of training for students who have graduated from intermediate schools, colleges, universities and after universities. In Vietnam and some countries around the world, continuing training is mandatory for health workers. Objective: Describe the results of continuous training and analyze some related factors at Bach Mai Hospital. Methods: Cross-sectional study, quantitative research. Results:This study collected information from 413 trainees, Bach Mai Hospital through questionnaires and retrospective data from student management records. The research results show that students’ knowledge and ability to apply knowledge/skills are quite good. Conclusion: The results of trainees at the end of the course are quite high (51.6%). The percentage of trainees who apply their trained knowledge/skills in practice is quite high (40-60% depending on the level of application). The rate of trainees giving a good assessment of the entire training activities is high (over 80%). There is a statistically significant relationship between age group, education level, occupation, employment status, trainees’ field of study and results of assessment of contents of continuing training activities. (p<0.05).